1968
DOI: 10.1063/1.1651906
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOEMISSION FROM InP-Cs-O

Abstract: Photoelectric measurements on cleaved p+ InP show that a process of cesiation and oxidation can produce a work function lower than the InP bandgap. Efficient photoemission results, with luminous efficiencies of 450 μA/lumen or better, and a threshold at 1.24 eV (1 μ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…4)to data (5), for neutral pions (WA80) and negative secondaries (HELIOS), respectively. The stars represent the pp data(25). The curves are drown simply to guide the eye.…”
mentioning
confidence: 99%
“…4)to data (5), for neutral pions (WA80) and negative secondaries (HELIOS), respectively. The stars represent the pp data(25). The curves are drown simply to guide the eye.…”
mentioning
confidence: 99%
“…Our experiments are consistent with out diffusion of Zn at about 650°C, and a sufficiently small loss of As at this heating temperature so as to result in negligible As vacancies near the surface of the crystal The very high quantum efficiency (500 /lA/lumen) of UHV-cleaved GaAs coated with Cs reported by Scheer and van Laar, 1 and the latter improvement of Turnbull and Evans,2 using combinations of Cs and O2, have been duplicated in this laboratory. 3 At the same time we have done considerable work in order to achieve similar performance on practical GaAs surfaces. Effects of sputtering are inconclusive; however, we found that heating at about 650°C produces highly clean surfaces.…”
Section: Ingaas-cso a Low Work Function (Less Than 10 Ev) Photoemitmentioning
confidence: 95%
“…J. Electron. 20,6 (1966); 20, 535 (1966).9 In the Schottky approximation, the bands bend 1 V in 100 A for ~ = 10 and p = 1 X 10 19 acceptors/cm 3. …”
mentioning
confidence: 98%
“…Further increases could be obtained by improving the escape probability. Quite high values have been reported, 0.97 for InP (Bell and Uebbing 1968) and 0.5 for GaInAs (Uebbing and Bell 1968), however, these figures are associated with very small escape depths and are more likely values for non-thermalized electrons (i.e. from upper conduction band minima), but the fact that values of 0-5 have been reported with coatings of CsF-Cs (Garbe 1969), albeit for cleaved material, do show that improvement could be possible.…”
Section: Escape Probabilitymentioning
confidence: 98%